Development of E-Learning Based Blogs on Global Warming Subject. (February 2019) - Mustari, M; Hoya, A L; Akmansyah, M; Diani, R; Asyhari, A
Abstract: The purpose of this study is to determine the feasibility of learning media with a blog in e-learning based and to identify students' of senior high school responses toward this media on the subject of global warming. The schools are located in Bandar Lampung, at SMAN 12 Bandar Lampung, SMAN 5 Bandar Lampung, and SMA Al Ahzar 3 Bandar Lampung. The research subjects were students of class XI SMA and questionnaire method is as data collection instruments, which was validated by the expert judgment method including material experts, media experts, and informatics experts. This type of data uses qualitative and quantitative data. The method in this study is the method of research and development according to Borg and Gall, which is only limited to 7 steps because can answer the problem. Based on data from expert judgment calculation and media feasibility response according to students, this media has quality of 85.25% (very feasible) according to material experts, 86% (very feasible) according to media experts, and 89% (very feasible) according to informatics experts, while the response of students to the attractiveness of learning media has very interesting interpretation criteria with a score of 94.8% in small group trials and 94.9% in field trials.